2017
DOI: 10.1556/004.2017.051
|View full text |Cite
|
Sign up to set email alerts
|

DNA of free-living bodonids (Euglenozoa: Kinetoplastea) in bat ectoparasites: potential relevance to the evolution of parasitic trypanosomatids

Abstract: Kinetoplastids are flagellated protozoa, including principally free-living bodonids and exclusively parasitic trypanosomatids. In the most species-rich genus, Trypanosoma, more than thirty species were found to infect bats worldwide. Bat trypanosomes are also known to have played a significant role in the evolution of T. cruzi, a species with high veterinary medical significance. Although preliminary data attested the occurrence of bat trypanosomes in Hungary, these were never sought for with molecular methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…1, in studied great ape feces. Although naturally free-living aquatic bodonids, the sister clade of parasitic trypanosomatids, have been very rarely identified in vertebrate hosts (for a review see Szőke et al, 2017 ), we believe that, in the present study, the occurrence of bodonids may be the result of secondary contamination of feces from the external environment or that the isolated DNA originated from bodonids present in water consumed by the apes.…”
Section: Discussionmentioning
confidence: 83%
“…1, in studied great ape feces. Although naturally free-living aquatic bodonids, the sister clade of parasitic trypanosomatids, have been very rarely identified in vertebrate hosts (for a review see Szőke et al, 2017 ), we believe that, in the present study, the occurrence of bodonids may be the result of secondary contamination of feces from the external environment or that the isolated DNA originated from bodonids present in water consumed by the apes.…”
Section: Discussionmentioning
confidence: 83%
“…However, environmental contamination cannot be ruled out, in a similar way to how Bodo sp. DNA was discovered in bats [49]. Woylies are ground dwelling herbivores feeding mostly on underground fungi [14], an environment in which Bodo sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the theory of trypanosomes evolving from free-living Bodo spp. [49] also needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…900 bp long fragment of the 18S (SSU) rRNA gene. The primers 609F (forward: 5′-CAC CCG CGG TAA TTC CAG C-3′) (da Silva et al 2004) and 706R (reverse: 5′-CTG AGA CTG TAA CCT CAA-3′) (Ramírez et al 2012) were used, as reported (Szőke et al 2017).…”
Section: Pcr Methodsmentioning
confidence: 99%